Design UI/UX Pemesanan Logam Mulia dengan Menggunakan Metode Design Thinking - Rudy Andree Hermawan; Nur Cahyo Wibowo; Seftin Fitri Ana Wati (International Forum of Researchers and Lecturers, 2024)
In the rapidly evolving digital era, the demand for precious metals, especially gold, has significantly increased. Companies need to adopt modern technology to facilitate the ordering of precious metals effectively and efficiently. This study aims to design the user interface (UI) and user experience (UX) of a precious metal ordering application using the Design Thinking method, which involves the stages of empathy, definition, ideation, prototyping, and testing. Starting with problem identification and interviews to understand user needs, this study produces user personas and user flows that assist in creating wireframes and mockups of the application. The prototype is tested through usability testing using the System Usability Scale (SUS) and Maze to measure user effectiveness, efficiency, and satisfaction. The results show that the designed application enhances user experience with an intuitive and easy-to-use interface, achieving a usability testing score of 85 on the SUS and a task success rate of 90% on Maze, indicating that the Design Thinking method is effective in designing the UI/UX of a precious metal ordering application.